Earth surface reflectivity climatology at 340–380 nm from TOMS data - Herman, Jay; Celarier, E. A. (AGU, 1997)
The 340–380 nm (UV) Lambertian equivalent reflectivities (LER) of the Earth's surface, between the latitudes ±70°, are constructed from 14.5 years of radiances measured by Nimbus-7/total ozone mapping spectrometer (November 1978 to May 1993). The surface LER values are obtained from the minimum reflectivity values for each 1°×1.25° (latitude × longitude) pixel with statistically improbable outlier values removed. The resulting LER climatology shows low surface reflectivity values over the entire globe at 340 and 380 nm that are nearly independent of wavelength (the difference is less than 0.2%). In general, the LER is lower over the land (2–4%) than over the oceans (5–8%), though both land and water have features outside of these ranges. Monthly maps of LER are derived that include seasonally persistent cloud features, as well as showing seasonal surface variations. There are low reflectivity regions in the ocean coastal waters that appear to be indicative of chlorophyll or silt from wave action or from rivers. There also are mid-ocean areas of comparatively high reflectivity with a seasonal variation that is not solar zenith angle dependent. These areas of high ocean reflectivity correlate with coastal zone color scanner observations that were associated with the absence of phytoplankton (clear water).